Connecting Gien Castle to its Landscape: Faunal, Environmental and Buildings Analyses (Loiret, France). (3rd July 2019) - Bizri, Mélinda; Jouanin, Gaëtan; Borderie, Quentin; Perrault, Christophe; Save, Sabrina; Vaughan-Williams, Alys
ABSTRACT: Gien castle is a listed monument of French architectural heritage. Today it houses the National Museum of Hunting and its collection. Organised visits to the site have traditionally lacked any clear mention of the castle's historical background. Recently, however, archaeological excavations and building analysis in 2011–2015 produced a wealth of new knowledge about the castle's medieval origins and history, and about its relationship to its landscape. During the ninth and tenth centuries and then in the fifteenth century the castle occupied a strategically exceptional position reflecting the connection with its environment, notably the strong connection between the castle settlement and the River Loire. These new readings of Gien's past landscapes diverge from the present-day identity of the castle as the 'National Museum of Hunting', and new connections need to be made.